2017
DOI: 10.1016/j.immuni.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Orchestrate pDC-XCR1+ Dendritic Cell Spatial and Functional Cooperativity to Optimize Priming

Abstract: Summary Adaptive cellular immunity is initiated by antigen-specific interactions between T lymphocytes and dendritic cells (DC). Plasmacytoid DC (pDC) support antiviral immunity by linking innate and adaptive immune responses. Here we examined pDC spatiotemporal dynamics during viral infection to uncover when, where and how they exert their functions. We found that pDC accumulated at sites of CD8+ T cell antigen-driven activation in a CCR5-dependent fashion. Furthermore, activated CD8+ T cells orchestrated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
238
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(272 citation statements)
references
References 47 publications
11
238
0
2
Order By: Relevance
“…3c, S2b). 4,7,44 Similarly, visualization of the migratory DC subsets confirmed previous observations, with CD207 + cells (Langerhans cells and migratory cDC1s) located within the central T cell zone, and the CD301b + and SIRPa + dermal DC (dDC) subsets located in regions bordering the B cell follicles and in the lower cortical ridge, respectively ( Fig. 3c, S2b).…”
Section: Myeloid Cell Organization In Steady State Lnssupporting
confidence: 88%
See 1 more Smart Citation
“…3c, S2b). 4,7,44 Similarly, visualization of the migratory DC subsets confirmed previous observations, with CD207 + cells (Langerhans cells and migratory cDC1s) located within the central T cell zone, and the CD301b + and SIRPa + dermal DC (dDC) subsets located in regions bordering the B cell follicles and in the lower cortical ridge, respectively ( Fig. 3c, S2b).…”
Section: Myeloid Cell Organization In Steady State Lnssupporting
confidence: 88%
“…Furthermore, quantitative analysis of resident cDC1 and cDC2 organization recapitulated previous findings, with preferential localization of resident cDC2 in the LN periphery and with more heterogeneous distribution of resident cDC1s across different LN compartments, including the T cell zone and some presence in the LN medulla. 4,5,[7][8][9]44,56 Intriguingly, as revealed by 3D vascular based neighborhood analysis, we found that both resident cDC1 and cDC2 subsets were also highly associated with LN blood vessels. Given the spatial segregation of these DC populations to different LN regions, we found that resident cDC1s and cDC2s were also associated with distinct vascular trees, with little local intermixing.…”
Section: Discussionsupporting
confidence: 53%
“…18 Expression of the XCR1 chemokine receptor is another conserved feature of cDC1 that enables close interaction with XCL-producing activated T cells and natural killer cells. Several recent studies indicate the importance of this axis in coordinating peripheral Th1 and cytotoxic responses 121,122 in reciprocity with the action of DCderived CXCL9/10 upon activated T cells. 123 In mice, cDC1 have also been characterized as crosspriming tolerogenic cells but this potential is not well documented in humans.…”
Section: Functions and Role In Immunitymentioning
confidence: 99%
“…However, how their professional IFN-I/III production precisely contributes to this protection remains to be deciphered. pDC role in shaping antiviral innate and adaptive immunity might supersede their contribution to the induction of IFN-I-dependent cell-intrinsic antiviral defenses, as recently proposed in various mouse models of viral infections (Swiecki et al, 2013;Cocita et al, 2015;Brewitz et al, 2017). During chronic viral infections in mice, macaques, and humans, pDC production of, and response to, IFN-I can play protective or deleterious roles (Tomasello et al, 2014).…”
Section: Introductionmentioning
confidence: 96%